The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.3389/fcvm.2018.00030
|View full text |Cite|
|
Sign up to set email alerts
|

Postnatal and Adult Aortic Heart Valves Have Distinctive Transcriptional Profiles Associated With Valve Tissue Growth and Maintenance Respectively

Abstract: Heart valves are organized connective tissues of high mechanical demand. They open and close over 100,000 times a day to preserve unidirectional blood flow by maintaining structure-function relationships throughout life. In affected individuals, structural failure compromises function and often leads to regurgitant blood flow and progressive heart failure. This is most common in degenerative valve disease due to age-related wear and tear, or congenital malformations. At present, the only effective treatment of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 52 publications
(55 reference statements)
0
7
0
Order By: Relevance
“…To examine this, we utilized the Fbn1 C1039G/+ mouse model that has previously been shown to exhibit thickened mitral valves by PND6.5 and develop systolic prolapse by 9 months of age [ 20 ]. From RNA-seq data, we have shown that Fbn1 is highly expressed in heart valves throughout life [ 34 ] and based on previous studies, it is anticipated that mRNA and protein levels do not change in mitral valves from Fbn1 C1039G/+ mice, but rather microfiber formation is impaired [ 22 ]. As shown in Figure 1 A–D, mitral valve leaflets from Fbn1 C1039G/+ pups at PND1 were grossly indistinguishable from wild type ( Fbn1 +/+ ) littermate controls ( Figure 1 B,M) by Pentachrome staining.…”
Section: Resultsmentioning
confidence: 99%
“…To examine this, we utilized the Fbn1 C1039G/+ mouse model that has previously been shown to exhibit thickened mitral valves by PND6.5 and develop systolic prolapse by 9 months of age [ 20 ]. From RNA-seq data, we have shown that Fbn1 is highly expressed in heart valves throughout life [ 34 ] and based on previous studies, it is anticipated that mRNA and protein levels do not change in mitral valves from Fbn1 C1039G/+ mice, but rather microfiber formation is impaired [ 22 ]. As shown in Figure 1 A–D, mitral valve leaflets from Fbn1 C1039G/+ pups at PND1 were grossly indistinguishable from wild type ( Fbn1 +/+ ) littermate controls ( Figure 1 B,M) by Pentachrome staining.…”
Section: Resultsmentioning
confidence: 99%
“…SFRP4 is a class I antagonist of the Wnt signaling pathways and has been reported to have antiproliferative effects and reduce fibrosis. [33,34] AMCF-II (or CXCL5) is a member of the CXC chemokine family and is associated with inflammation and valve calcification. [35] Both MMP and ADAMTS are major proteinase enzymes that are required for heart valve development, repair, and remodeling.…”
Section: Rna Sequencing Analysismentioning
confidence: 99%
“…3 After embryonic maturation, these cells convert into a quiescent phenotype and in the absence of diseases maintain physiological turnover of the extracellular matrix to provide efficient function throughout life. 4 However, the mechanisms that regulate postnatal valve growth and remodelling as well as adult homeostasis are poorly understood. We believe that these findings, if confirmed, are relevant because they may indicate that the altered metabolic and endocrine milieu of type 1 diabetes may interfere with those mechanisms that maintain growth and remodelling of the aortic valve during childhood.…”
Section: Impaired Aortic Valve Growth In Type 1 Diabetes Mellitusmentioning
confidence: 99%